2013
DOI: 10.1037/a0031277
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic auditory stimulation influences syntactic processing in children with developmental language disorders.

Abstract: Together with previous findings on deficits in temporal processing and sequencing, as well as with the recent proposition of a temporal sampling (oscillatory) framework for developmental language disorders (U. A. Goswami, 2011, Temporal sampling framework for developmental dyslexia, Trends in Cognitive Sciences, Vol. 15, pp. 3-10), our results point to potential avenues in using rhythmic structures (even in nonverbal materials) to boost linguistic structure processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
159
4
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(193 citation statements)
references
References 106 publications
25
159
4
5
Order By: Relevance
“…If we take the interaction process seriously, as well as the complexity that underlies our dynamical embodiment, treatments of cognitive disorders might be improved. For example, rhythmic auditory stimulations improve the linguistic performances of children diagnosed with developmental language disorders (Przybylski et al, 2013). Further, fractal metrics can distinguish between dyslexic and normal readers in a word-naming task (Wijnants et al, 2012).…”
Section: Conclusive Discussionmentioning
confidence: 99%
“…If we take the interaction process seriously, as well as the complexity that underlies our dynamical embodiment, treatments of cognitive disorders might be improved. For example, rhythmic auditory stimulations improve the linguistic performances of children diagnosed with developmental language disorders (Przybylski et al, 2013). Further, fractal metrics can distinguish between dyslexic and normal readers in a word-naming task (Wijnants et al, 2012).…”
Section: Conclusive Discussionmentioning
confidence: 99%
“…For instance, an intriguing study used musical rhythms to invoke auditory rhythmic stimulation in alternating blocks of trials and spoken sentences, and found that children with both typical and atypical language development were better able to detect syntactic violations in sentence trials that were heard after a block of musical stimuli that had regular (versus irregular) rhythms. 33 …”
Section: Brain Evidence That Rhythm Modulates Syntactic Processingmentioning
confidence: 99%
“…We typically acquire a language by first listening to it, and then by speaking it, before developing reading and writing skills (Harris, 1947). The perception of rhythm is emerging as being particularly relevant to both the normal acquisition of language skill and disorders of language (e.g., Huss et al, 2011; Grube et al, 2012, 2013, 2014; Przybylski et al, 2013; Gordon et al, 2015; Wieland et al, 2015). …”
Section: Introductionmentioning
confidence: 99%